A novel mechanism for TNF-alpha regulation by p38 MAPK: involvement of NF-kappa B with implications for therapy in rheumatoid arthritis. - Campbell, J; Ciesielski, C; Hunt, A; Horwood, N; Beech, J; Hayes, L; Denys, A; Feldmann, M; Brennan, F; Foxwell, B (2004)
TNF-alpha is a key factor in a variety of inflammatory diseases. This study examines the role of p38 MAPK in the regulation of TNF-alpha in primary human cells relevant to inflammation, e.g., macrophages and rheumatoid synovial cells. Using a dominant negative variant (D168A) of p38 MAPK and a kinase inhibitor, SB203580, we confirm in primary human macrophages that p38 MAPK regulates TNF-alpha production using a posttranscriptional mechanism requiring the 3' untranslated region of the gene. However, in LPS-activated primary human macrophages we also detect a second previously unidentified mechanism, the p38 MAPK modulation of TNF-alpha transcription. This is mediated through p38 MAPK regulation of NF-kappaB. Interestingly this mechanism was not observed in rheumatoid synovial cells. Importantly however, the dominant negative mutant of p38 MAPK, but not SB203580 was effective at inhibiting spontaneous TNF-alpha production in these ex vivo rheumatoid synovial cell cultures. These data indicate there are potential major differences in the role of p38 MAPK in inflammatory signaling that have a bearing on the use of this kinase as a target for therapy. These results indicate despite disappointing results with p38 MAPK inhibitors in the clinic, this kinase is a valid target in rheumatoid disease.